(untitled) (Global Journal of Science Frontier Research, 2023)
The Paris Agreement signed in 2015 during the 21st Conference of the Parties COP21 of the United Nations Framework Convention was an important milestone for the establishment of ambitious and concrete climate goals especially with regard to the reduction of greenhouse gas emissions effect and energy security To this end several countries committed to achieving the goals established by the Paris Agreement are in the energy transition phase from a carbon-based matrix to a cleaner low-carbon matrix In this context green hydrogen emerges as a clean energy alternative being a favorable option to move towards the current process of decarbonization of global economies in particular industries and the mobility sector and to achieve the goals established in the Agreement Brazil in turn prepared an energy expansion plan to compose its matrix with a 45 share of clean energy by the year 2030 however with regard to the use of green hydrogen as a direct source of energy or energy vector the country is still in the incipient stage of research and development R D Currently Brazil has a very diversified energy matrix concentrating a high installed capacity for generating energy from clean sources such as wind solar photovoltaic hydro biomass which has made it possible as a promising region for the development and production of hydrogen green